Analisa Kinerja Chatgpt Dalam Menghasilkan Teks Bahasa Indonesia Menggunakan Metode Support Vector Machines (SVM) - Tony Baskoro; Nuddin, Salamun Rohman (Universitas Negeri Surabaya, 2025)
The development of natural language processing technology has opened opportunities for creating language models such as ChatGPT, which can generate text in various languages, including Indonesian. This study focuses on evaluating the performance of ChatGPT in generating Indonesian-language text using the Support Vector Machines (SVM) approach. The dataset used consists of [number of data entries] text entries across various categories, namely